Impact of colorectal cancer screening on cancer-specific mortality in Europe: A systematic review - Gini, Andrea; Jansen, Erik E.L.; Zielonke, Nadine; Meester, Reinier G.S.; Senore, Carlo; Anttila, Ahti; Segnan, Nereo; Mlakar, Dominika Novak; de Koning, Harry J.; Lansdorp-Vogelaar, Iris; Veerus, Piret; Anttila, Ahti; et al. (European journal of cancer (1990), 2020)
Populations differ with respect to their cancer risk and screening preferences, which may influence the performance of colorectal cancer (CRC) screening programs. This review aims to systematically compare the mortality effect of CRC screening across European regions. Six databases including Embase, Medline, Web of Science, PubMed publisher, Google Scholar and Cochrane Library were searched for relevant studies published before March 2018. Bibliographic searches were conducted to select studies assessing the effect of various screening tests (guaiac fecal occult blood test [gFOBT]; flexible sigmoidoscopy [FS]; fecal immunochemical test [FIT] and colonoscopy) on CRC mortality in Europe (PROSPERO protocol: CRD42016042433). Abstract reviewing, data extraction and risk of bias assessment were conducted independently by two reviewers. A total of 18 studies were included; of which, 11 were related to gFOBT, 4 to FS, 2 to FIT and 1 to colonoscopy; 8 were randomised clinical trials, and 10, observational studies, and an approximately equal number of studies represented Northern, Western and Southern European regions. Among individuals invited to screening, CRC mortality reductions varied from 8% to 16% for gFOBT and from 21% to 30% for FS. When studies with a high risk of bias were considered, ranges were more extensive. The estimated effectiveness of gFOBT and FS screening appeared similar across different European regions. CRC mortality impact of inviting individuals with similar adopted screening strategies (gFOBT or FS) may be consistent across several European settings. •Populations differ with respect to their cancer risk and screening preferences.•This systematic review assessed published evidence of colorectal cancer screening in Europe.•Screening studies from Northern, Western and Southern European regions were reviewed.•Similar adopted screening strategies (guaiac fecal occult blood test or flexible sigmoidoscopy) may have a consistent impact across Europe.